Analysis of Energy Performance Indicators Based on ISO 50001-2018 in Shopping Centers Using RETScreen Expert - Turinno, Sarwo; Mochammad Facta; Cahyadi, (International Journal of Scientific Research and Management (IJSRM), 2024)
The ISO 50001 energy management system has been implemented by many organizations around the world, including in Indonesia. The purpose of this application is to sustainably improve energy performance to reduce energy consumption and energy costs. In determining the measurement of energy performance improvement, energy performance indicators and energy baseline are used. This study will analyze the energy performance indicators obtained from the energy audit results of one shopping center in Indonesia using RETScreen Expert software. Multiple linear regression is used to develop the energy baseline equation and examine the relationship between energy consumption and significantly influencing variables, such as Service Usage (person) and Cooling Degree Days (CDD). This baseline equation will be used to monitor energy performance after energy performance improvement measures are taken. From the results of this equation, the predicted value of energy consumption in 2023 after improving energy performance in 2022 is 7,014,081 kWh then from the actual measurement results obtained energy consumption value of 6,113,632 kWh the results of the calculation of energy savings obtained from the energy baseline equation using RETScreen Expert software is 900,449 kWh / year.